FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPUASAN PASIEN RAWAT JALAN DI PUSKESMAS BATANG III - Imam Purnomo; Zaenal Amirudin; Supriyo . (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2014)
Patient  satisfaction  is  a  person's  level  of  perceived  circumstances  that  are  the  result  of comparing  the  performance  or  outcome  of  product  perceived  in  relation  to  one's  expectations. Stem health center III is one of the health service which is visited by patients. Based on data from patient  visits in the last 3  months (January-March 2013) also found a decrease in the number of visits or tend to be unstable. That was in January, as many as 229 patients, more than 254 patients in February and March, as many as 171 patients. With the picture of the researcher interested in taking a research on the factors - factors related to outpatient satisfaction in Batang health center III. This  study  used  a  descriptive  cross  sectional  analytic  approach  to  the  interview  using  a questionnaire.  Based  on  the  survey  results  revealed  There  is  a  relationship  between  Reliability, Responsiveness, Empaty, Assurance, Tangible, perceived benefits, perceived barriers to outpatient satisfaction in Batang health center III. Suggestions in this research is expected that officers should be more concerned about the patient's health  and  help  trouble  when  patients  need  information  about  health  center  III  Rod  and  provide packets of information, including cost information packet, when it comes to Batang health center patients  III  should  immediately  give  a  greeting  or  welcome  and  officers  provide  information  to customers carefully and answer clearly any complaints, criticisms and suggestions  from patients, health  centers  intensify  Batang  health  center  III  so  that  for  patients  who  are  far  away  from  the Batang health center III does not need to be expensive for reaching health centers. Keywords: Satisfaction, Patient of Batang Health Center III